2009
DOI: 10.1007/s11661-009-9785-5
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structure Evolution and Abnormal Wear Behavior of the TiNiNb Alloy under Impact Load

Abstract: The TiNiNb alloy exhibits a linear increase in wear with a number of impacts at the low impact energy density E im of 1.6 J/cm 2 . However, a change in the volume wear occurs on the wear curve when E im is increased to 2.42 J/cm 2 . In this case, when the number of impacts N is more than 3 9 10 5 cycles, the wear rate decreases from 5.8 9 10 À6 to 1.9 9 10 À6 mm 3 /cycle, which is only one-half of that under low E im (1.6 J/cm 2 ). It is significant for practical applications because impact energy increases wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…It is interesting that for some higher strength materials (for example, the four materials in this study) at a relatively low impact energy the subsurface cracks could be found, while at the high impact energy density the cracks after turning could not. This has been confirmed by authors' experiments [21][22][23][24][25][26]. It can be only explained as follows.…”
Section: Relation Between Quasi-nano and Delamination Wear Mechanismsupporting
confidence: 70%
“…It is interesting that for some higher strength materials (for example, the four materials in this study) at a relatively low impact energy the subsurface cracks could be found, while at the high impact energy density the cracks after turning could not. This has been confirmed by authors' experiments [21][22][23][24][25][26]. It can be only explained as follows.…”
Section: Relation Between Quasi-nano and Delamination Wear Mechanismsupporting
confidence: 70%